Analysis of The Ionic Bond and Related Concept in High School Chemistry Textbooks in Pekanbaru - Ardiansyah, Ardiansyah; Fitriyani, Indah (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Misconceptions about ionic bonding bond and related concept have been revealed by many studies. One source of student misconceptions is high school chemistry textbooks. This research aims to analyze the ionic bonding conceptions contained in Class X high school chemistry textbooks in the city of Pekanbaru. This research uses document analysis techniques. The research sample was 5 high school chemistry books for class X in Pekanbaru City. Misconception are grouped according to Hershey (2004), namely Oversimplifications, Overgeneralizations, Obsolete Concepts and Terms, Misidentifications, and Flawed Research. Most textbooks suffer from Overgeneralizations of the concepts of  chemical stability, ionic bonds, and properties of ionic compound.